2012
DOI: 10.1007/s11746-012-2144-5
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Equilibria in Biodiesel Production

Abstract: During biodiesel production, the product is contaminated with impurities such as some non‐reacted alcohol, glycerol, and catalyst. In order to comply with product requirements, these impurities must be removed, for example, by washing with water. Knowledge of the extent of water solubility in biodiesel is required to design the drying system and determine fuel quality. In the present work, the solubilities of water in biodiesels produced from sunflower and canola oils were measured within the temperature range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 10 publications
4
17
0
Order By: Relevance
“…The formation of heterophases of FG under these circumstances comes as a surprise because earlier work indicates the solubility of FG is much higher than allowable maximum levels in ASTM or EN specifications. The earlier measurements [31,32] are based upon the results of titrations, and lack the sensitivity and specificity needed for definitive results at levels between 0.000 and 0.020%. According to a US DOE survey of 67 commercially available B100s, these are levels that can be found in the US [43].…”
Section: Equilibrium Solubility Of Fg and Liquid Glycerin In Famementioning
confidence: 99%
See 1 more Smart Citation
“…The formation of heterophases of FG under these circumstances comes as a surprise because earlier work indicates the solubility of FG is much higher than allowable maximum levels in ASTM or EN specifications. The earlier measurements [31,32] are based upon the results of titrations, and lack the sensitivity and specificity needed for definitive results at levels between 0.000 and 0.020%. According to a US DOE survey of 67 commercially available B100s, these are levels that can be found in the US [43].…”
Section: Equilibrium Solubility Of Fg and Liquid Glycerin In Famementioning
confidence: 99%
“…Published values for the solubility of FG in purified B100 are scarce, despite the recognized importance of solubility limitations in the separation/purification processes. Two publications report actual measurements in B100 using titration methods, and indicate a solubility of 0.2% at 20 °C [31] and less than 0.15% [32] or up to 10 times above the current international limits of 0.020% [5,6]. These reported high solubilities can encourage the expectation of a homogenously distributed dissolved FG content during sampling for routine quality checks.…”
Section: Introductionmentioning
confidence: 99%
“…9−14 This mixture, which also contains significant amounts of unreacted alcohol, is then taken to the separation and purification units. 15,16 In the separation section, glycerol and biodiesel are usually separated by decantation, and we can distinguish between two phases: one glycerol-rich phase and one ester-rich phase, noting that unreacted alcohol is distributed in both phases. 17 One important characteristic of the separation section that needs investigation is the extent of the miscibility between biodiesel, glycerol, and the unreacted alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, liquid−liquid equilibrium experimental data were correlated with fitted NRTL, UNIQUAC, and UNIFAC models to produce mean square deviations in composition of 1.34% for the NRTL, 1.34% for the UNIQUAC, and 4.13% for the UNIFAC model. Rostami et al 16 carried out the study of the liquid−liquid equilibrium of ternary systems involving sunflower/canola biodiesel−glycerol−methanol at 293.15, 303.15, and 313.15 K. They reported that the region of immiscibility decreased with increasing temperature and concluded that losses of biodiesel during purification were small if this unit is operated at low temperatures. They used the UNIQUAC model with parameters fitted to experimental data to predict the behavior of the binary and ternary systems, where the binary interaction coefficients were further optimized for each system to increase accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies of the liquid‐liquid equilibrium (LLE) are carried out together with thermodynamic modeling. Activity coefficient models such as UNIFAC, UNIQUAC, and NRTL have been successfully applied to liquid‐liquid systems to find the relationships between experimental data . In this study, an experimental study and thermodynamic modeling were performed on a ternary‐component system of glycerin + methanol + organic solvent (toluene, petroleum ether, and n ‐butanol).…”
Section: Introductionmentioning
confidence: 99%